New records of Reduviidae (Hemiptera: Heteroptera) from Brazil - Gil-Santana, Hélcio R. (Zootaxa, 2007)
New occurrences of Reduviidae from Brazil are recorded for the first time: Ectrichodiinae: Borgmeierina dentata  Wygodzinsky, Parapothea jaguaris Carpintero (new genera records); Harpactorinae: Aristathlus imperatorius Bergroth,  Aristathlus regalis Bergroth (new genus record), Notocyrtus foveatus Stål, Orbella tricolor Maldonado, Sosius foliaceus  Champion; Reduviinae: Zelurus salyavatoides Lent & Wygodzinsky; Saicinae: Tagalis seminigra Champion; Stenopodainae:  Achillas toulgoeti Bérenger (new genus record).